Clinico-Histopathological Correlation of Non-NeoplasticDermatological Lesions - Vibhuti Kumar; Anita Sharan; Sunita Poriya; Sonia kundu (International Journal of Medical Research and Review, 2022)
Objective: Non-neoplastic skin disorders are more common than neoplastic skin disorders whichhave included Infectious diseases, non-infectious erythematous lesions, papular & squamousdisorders, connective tissue diseases, non-infectious vesiculobullous / Vesiculopustular disorderse.tc. The pattern of skin diseases varies from one country to another and across different parts ofthe same country. So due to the variable spectrum, the histopathology of skin diseases is varied.Each clinical presentation is common to different histopathological pictures & thus definitely requireshistopathology for confirmation. Design: This study was conducted by Dr D. Y. Patil Medical Collegeand Hospital, Navi Mumbai from October 2018 to October 2020. Subjects: One hundred and fiftynon-neoplastic specimens of skin biopsies submitted in the histopathology; Department of Pathologywere considered as the subjects of the study. Material and Methods: Histopathological resultswere presented in tabular and graphical forms. Mean, median, standard deviation and ranges werecalculated for quantitative data. The Chi-square test and t-test with p<0.001 was consideredsignificant. Results: The mean age of our study participants was 41.9 years with a standarddeviation of 36.5 years. The majority of our study participants were females: 29.4 % of patientspresented with infectious lesions, 22.7 % of patients presented with papulosquamous lesions, and12.7 % of patients presented with vesiculobullous lesions. The most common infectious non-neoplastic skin lesion was leprosy, the most common papulosquamous skin lesion was dermatitis,and the commonest vesiculobullous skin lesion was Pemphigus Vulgaris. Conclusion: An integratedapproach by dermatologists and pathologists is recommended to increase the accuracy of diagnosisand for better management of the patient